Competitiveness analysis of coconut commodity in gorontalo: market and product diversification review - Rismanto Rismanto; Abdul Latif (Jurnal Mantik, 2024)
This research delves deeply into the realm of product diversification strategies within Gorontalo Province's coconut sector, emphasizing coconuts' foundational role in the region's economy. Through an exhaustive literature review, the study dissects the key determinants influencing coconut competitiveness, encompassing evolving global market trends, intricate trade regulations, and the imperative of product innovation. Highlighting the pressing need for diversification in an increasingly competitive global landscape, the research illuminates challenges and opportunities specific to the coconut sector in Gorontalo. Such insights not only inform stakeholders but also furnish essential strategic directives for formulating robust local economic policies, ensuring the sector's sustained growth and competitiveness amidst global challenges.